2010
DOI: 10.2139/ssrn.1635698
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Entry Conditions, Wages and Job Mobility

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…17 While initial wages vary depending on the birth cohort, it is quite obvious that irrespective of one's sex, daily wages tend to follow a positive trend over the lifecycle. This observation is comparable to other studies that look at cohort-specific labormarket performance over the lifecycle (e.g., Bachmann, Bauer and David [2010] Figure 3 show the probability of being drafted by month of birth for males. The points on the graph represent the share of men who were drafted for each month-year cohort.…”
Section: Data Descriptionsupporting
confidence: 88%
“…17 While initial wages vary depending on the birth cohort, it is quite obvious that irrespective of one's sex, daily wages tend to follow a positive trend over the lifecycle. This observation is comparable to other studies that look at cohort-specific labormarket performance over the lifecycle (e.g., Bachmann, Bauer and David [2010] Figure 3 show the probability of being drafted by month of birth for males. The points on the graph represent the share of men who were drafted for each month-year cohort.…”
Section: Data Descriptionsupporting
confidence: 88%
“…32 Our mobility results contrast strongly with those from Bachmann et al (2010) for Germany (similar results are reported by Oreopoulos et al (2006Oreopoulos et al ( , 2008 for the US), who find that workers entering during poor entry conditions switch employers more often later on.…”
Section: Discussionsupporting
confidence: 41%
“…This is particularly worrying since evidence on past recessions demonstrates a substantial and long-lived negative influence of labour market entry in a recession on future wages and employment outcomes. This is, for example, shown by von Wachter and Bender (2008) in their analysis of the labour market history of German workers, and for West Germany as a whole by Bachmann et al (2010). The latter authors find that labour market entrants earning less than the average starting wage are more likely to change their job as well as their occupation.…”
Section: Related Literaturementioning
confidence: 78%